2020
DOI: 10.3390/jfb11020028
|View full text |Cite
|
Sign up to set email alerts
|

Open-Cell Tizr-Based Bulk Metallic Glass Scaffolds with Excellent Biocompatibility and Suitable Mechanical Properties for Biomedical Application

Abstract: A series of biocompatible high-porosity (up to 72.4%) TiZr-based porous bulk metallic glass (BMG) scaffolds were successfully fabricated by hot pressing a mixture of toxic element-free TiZr-based BMG powder and an Al particle space holder. The morphology of the fabricated scaffolds was similar to that of human bones, with pore sizes ranging from 75 to 250 μm. X-ray diffraction patterns and transmission electron microscopy images indicated that the amorphous structure of the TiZr-based BMG scaffolds remained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The parameters of the hot press process in sintering include the hot press temperature, holding time, and pressure. Under the same hot press temperature, holding time, and pressure, the high thermal conductivity of materials presented a stronger bonding interface between the particles and mechanical properties [ 13 , 14 , 26 ]. In other words, a material with a higher thermal conductivity would require a lower hot press temperature and holding time to fabricate a material with a uniform structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameters of the hot press process in sintering include the hot press temperature, holding time, and pressure. Under the same hot press temperature, holding time, and pressure, the high thermal conductivity of materials presented a stronger bonding interface between the particles and mechanical properties [ 13 , 14 , 26 ]. In other words, a material with a higher thermal conductivity would require a lower hot press temperature and holding time to fabricate a material with a uniform structure.…”
Section: Discussionmentioning
confidence: 99%
“… , , , and are dependent on the bonding-force interface between amorphous metallic glass particles and the structure of porous samples. Our previous study reported that the , , and of Ti 42 Zr 35 Ta 3 Si 5 Co 12.5 Sn 2.5 BMG foams were approximately 112 GPa, 1342 MPa, and 6.08 g/cm 3 , respectively [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that adding the Zr element in TiZr-based BMG alloy can make GFA increased without reducing other properties [12][13][14]. Our previous studies [15][16] reported biocompatible TiZr-based BMGFs with the composition of Ti 42 Zr 35 Si 5 Ta 3 Co 12.5 Sn 2.5 were fabricated by the hot-pressing method. The spacer holder method was selected for fabricating bulk samples and then removed to generate porous samples.…”
Section: Introductionmentioning
confidence: 99%